PROTECTIVE EFFECT ETHANOLIC EXTRACT OF Boesenbergia pandurata (ROXB.) Schlecht. AGAINST UVB-INDUCED DNA DAMAGES IN BALB/C MICE - Shanti Listyawati; Sismindari Sismindari; Sofia Mubarika; Yosi Bayu Murti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Boesenbergia pandurata (Roxb.) Schlecht. contains bioactive compounds that have a number healthy effect including anti-oxidant and anti-carcinogenic activity. This research was carried out to examine the protective effect of B. pandurata extract against expression of cyclobutane pyrimidine dimers (CPDs) as marker of UVB-induced DNA damage in Balb/c mice. Dried powder of B. pandurata rhizomes was extracted by maceration method using 96% ethanol. The extract was quantified with pinostrobin as active marker using TLC scanner. Ethanolic extract of B. pandurata (EEBP) was given orally at 14 days before UV exposure with a variety doses, 0 (vehicle), 20, 40 and 60mg/kgBW/day and continuing until termination of the experiment. Following the UVB irradiation (1.4J/m2), mice were sacrificed at different time points (2, 24, 48, and 72h after UVB exposure). The back skin samples were collected to analyze CPDs expression by immunohistochemical method. The result showed that EEBP (contained 5% pinostrobin) dose was 40 and 60mg/kgBW/day had protective activity against UV-induced DNA damage as indicated by the decrease of CPDs expression. Key words: Boesenbergia pandurata (Roxb.) Schlecht., UVB, DNA damage, CPDs.